Bringing Value at the Physical and Mental Health Interface: A Retrospective Record-based Research of Diagnostic Concordance between Physicians/Surgeons and Psychiatrists - Yogender Kumar Malik; Adwitiya Ray; Sujata Sethi; Rajiv Gupta (Annals of Indian Psychiatry)
Introduction: Consultation-liaison psychiatry (CLP) serves as a vital bridge between psychiatric and medical specialties, offering expert opinions and educational support. Despite high psychiatric comorbidities, referral rates in most parts of the world remain low. Poor psychiatric awareness, stemming from inadequate undergraduate psychiatric training, may contribute to the difficulty in detecting these symptoms. Studying concordance between psychiatric diagnoses made by referring doctors and psychiatrists can shed light on this area. Aims: This study aims to explore the concordance between diagnoses made by physicians and psychiatrists. Settings and Design: A 3-year retrospective record-based research was conducted at a tertiary care center. Methods: The study focused on in-patient referrals to the CLP unit. Data from 2917 referral calls included demographic profiles, referral reasons, and diagnoses. The Concordance was assessed using kappa statistics, with interpretation based on Landis and Koch’s criteria. Results: Delirium emerged as the most frequent psychiatric diagnosis, followed by depressive disorders, alcohol dependence, adjustment disorder, and opioid dependence. Referral patterns showed limited use of specific psychiatric terms by physicians (5.9%). Concordance varied across diagnoses, with substance use and intentional self-harm displaying substantial agreement, while delirium and depression had lower concordance. Conclusion: The study highlights the prevalence of delirium in CLP referrals and emphasizes the need for collaboration between CLPs and physicians. It also reveals a limited use of specific psychiatric diagnoses by referring doctors, suggesting potential gaps in psychiatric awareness. The findings underscore the importance of targeted educational interventions and increased collaboration to enhance diagnostic accuracy and patient outcomes.